Principles of organizing a surgical list. Issue 4 (April 2017) - Lin, Zoe; Moore, Timothy J.
Abstract: The principles of organizing a theatre list are based on a multidisciplinary, safety-centred approach to patient care and require a surgeon to have good organizational, communication and leadership skills. It is important to understand the processes and protocols required to ensure patient safety and maintain theatre efficiency, as well as the various patient-specific and operation-specific factors that need to be considered when booking cases. This article aims to cover the various steps through a patient's journey from the decision to treat through to aftercare, highlighting the factors that the surgeon should consider at each stage. They include the preoperative planning process from pre-assessment to booking cases, and embraces day-of-surgery issues from team briefing to the perioperative care of the patient's co-morbidities. Preoperative planning is essential in the complexity of modern day surgery to ensure patient safety and maintain theatre efficiency. The contemporary surgeon should be prepared constantly to evolve processes and improve team skills to enhance their patient's experiences and outcomes. A thorough grasp of the principles behind running an operating list is vital for the maintenance of good surgical practice.